Keberlanjutan Pariwisata di Pesisir Selatan Kabupaten Bantul - hasanah, nurdita (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Sustainable development considers sustainability as a balance between the need and availability of resources that allows the co-existence of humans, nature, and the environment in the present and future. Tourism has positive and negative impacts on sustainability. In particular, coastal tourism has the natural potential as tourism attraction but also has the risk of disaster, which affect the sustainability. This research aims to identify the level of sustainability and the most influencing factors for the level of sustainability of coastal tourism. This research was conducted in coastal areas that are part of the South Coast tourism development area in Bantul Regency. This research was conducted employing a quantitative deductive method using 10 indicators that represent environmental, economic, sosio cultural and transversal components. Data was collected through observation, interviews, and questionnaires from 128 tourism who visited coastal tourism destination using purposive sampling. Data analysis was carried out in the form of variable scoring, sustainability assessment, descriptive analysis, variable testing, and discriminant analysis. The result showed that the Southern Coast of Bantul Regency was less sustainable. From the four components of sustainability, environmental and economic components affect tourism sustainability. The most influencing factors for sustainability are natural resource management, waste management and destination attractiveness. Keywords: factor, sustainability, tourism, coast